Spatial and temporal fuels changes in whitebark pine (Pinus albicaulis) from mountain pine beetle (Dendroctonus ponderosae) - Gray, Curtis A.; Toone, Chelsea; Jenkins, Michael J.; Null, Sarah E.; Yocom, Larissa L. (Forest ecology and management, 2021)
•Mountain pine beetle has caused extensive tree mortality in whitebark pine.•We evaluated changes to surface fuels and foliar moisture infested trees.•Tree crowns and bark beetle condition class were mapped for multiple years.•Hot spot/spatial point pattern analysis was used to quantify spatial changes to fuels.•Hot spot analysis revealed increased fuel hazard in trees 2–3 years post beetle attack. Mountain pine beetle (MPB; Dendroctonus ponderosae Hopkins) causes extensive tree mortality in whitebark pine (Pinus albicaulis Engelm) forests. Previous studies conducted in lodgepole pine (Pinus contorta Douglas), Douglas-fir (Pseudotsuga menziesii (mirb.) Franco), and Engelmann spruce (Picea engelmanni Parry ex. Engelm) have shown that litter, duff, and 1-h (<0.64 cm) and 10-h (0.64–2.54 cm) time lag fuels are altered significantly from MPB outbreaks, while coarse woody fuels are affected over a longer time frame. MPB activity in conifer stands also alters foliar fuel moisture content over the course of the bark beetle rotation. This study evaluated changes to fine surface fuels and foliar fuel moisture in and under whitebark pine trees infested by MPB at two sites in Montana and Wyoming, USA. Fuel loads and foliar moisture were measured for crown condition classes of green trees (healthy), red trees (within two years since initial MPB attack with at least 50% of needles remaining), and gray trees (more than two years since attack with approximately 15% to 45% needles remaining). Tree locations and condition class were mapped using 2011, 2013, and 2015 NAIP imagery, and spatial point patterns were identified. Duff depths were significantly shallower beneath green trees (10.7–11.9 mm) than red (16.7–17.7 mm) and gray (13.9–16.1 mm) trees. Foliar fuel moisture content was altered dramatically across crown condition classes. Red needled trees had the lowest fuel moisture content, which was less than 18%. Point pattern hot spot analysis revealed increased (hot-spots) fuel hazard in trees 2–3 years post MPB attack, and decreased fuel hazard (cold-spots) in trees more than 3 years after MPB attack because foliage fell from trees and left larger diameter aerial fuels which were less likely to ignite. MPB-attacked trees were often clustered, and thus fuels hazard was not uniform across the landscape following MPB attack.